2018
DOI: 10.1038/s41401-018-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits the proliferation of hepatoma cells through controlling GLUT1-mediated glucose metabolism

Abstract: Aspirin can efficiently inhibit liver cancer growth, but the mechanism is poorly understood. In this study, we report that aspirin modulates glucose uptake through downregulating glucose transporter 1 (GLUT1), leading to the inhibition of hepatoma cell proliferation. Our data showed that aspirin significantly decreased the levels of reactive oxygen species (ROS) and glucose consumption in hepatoma cells. Interestingly, we identified that GLUT1 and HIF1α could be decreased by aspirin. Mechanically, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 55 publications
1
42
0
1
Order By: Relevance
“…Dalton's lymphoma (T-cell lymphoma) cells obtained from tumor-bearing mice treated by aspirin showed a change of expression of pH regulators MCT-1 and V-ATPase, as well as change in cell survival regulatory molecules including GLUT-1 (131). Aspirin can also modulate glucose uptake by depressing GLUT-1 through targeting NF-κB or NF κB/HIF1α signaling to inhibit proliferation (132).…”
Section: Application Of Glucose Metabolism In Cancer Treatmentmentioning
confidence: 99%
“…Dalton's lymphoma (T-cell lymphoma) cells obtained from tumor-bearing mice treated by aspirin showed a change of expression of pH regulators MCT-1 and V-ATPase, as well as change in cell survival regulatory molecules including GLUT-1 (131). Aspirin can also modulate glucose uptake by depressing GLUT-1 through targeting NF-κB or NF κB/HIF1α signaling to inhibit proliferation (132).…”
Section: Application Of Glucose Metabolism In Cancer Treatmentmentioning
confidence: 99%
“…This effect of ASA is currently explained by its ability to acetylate proteins other than COX-1 [38]. Recently, it has been demonstrated that ASA also decreases the expression of the hypoxia-inducible factor 1alpha (HIF1α), a key regulator of genes that are involved in metabolism under hypoxic conditions and a major determinant of tumor cell stabilization [39,40]. In a recent report [41], it has been shown that under normoxic conditions, HIF1α activity is significantly increased by glutamine metabolism, and is decreased by (a) acetylation via acetyl CoA synthetase or ATP citrate lyase, and (b) the presence of L-ascorbic acid, citrate, or acetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin (Sigma-Aldrich, St. Louis, MO, USA) was dissolved in dimethyl sulfoxide (DMSO) (Sigma-Aldrich, St. Louis, MO, USA). Given that the aspirin treatment mainly referred to the previous studies in HEK293T cells [35], HepG2 cells [36,37] and B16 cells [38], 2.5 mM aspirin was added into HEK293T, HepG2 and B16 cells for 48 h. After aspirin treatment for 48 h, cells were collected after trypsin digestion and low-speed centrifugation (800 rpm, 5 min). To exclude the effect of residual drugs, cells were washed twice using phosphate buffer saline.…”
Section: Cell Experimentsmentioning
confidence: 99%